Influence Of Suckling And Nutrition On Resumption Of Postpartum Ovarian Activity In Swamp Buffaloes (Bubalus Bubalis) - Yusof, Nordin (1993)
Four studies were conducted to evaluate the reproductive performance and factors affecting the resumption of postpartum ovarian activity in swamp buffaloes. The reproductive performance of swamp buffaloes (n=104) under an extensive production system was evaluated using calving records from 1977 to 1990 (Study 1). The calving to conception interval (n=117) and the intercalving interval (n=117) of the buffaloes were 177 and 489 days respectively. There was no influence of rainfall on the occurrence of conceptions in the animals. The dry matter intake, ovarian activity determined by plasma progesterone (P4) profiles, body weight and body condition changes postpartum in swamp buffaloes (n=12) under an extensive production system were assessed (Study 2). Delayed resumption of postpartum ovarian activity was confirmed as one reason for the long calving interval in suckled buffaloes under the extensive production system.